Phytolith Radiocarbon Dating: A Review of Previous Studies in China and the Current State of the Debate - Zuo, Xinxin; Lu, Houyuan (Frontiers in Plant Science, 2019)
Phytolith radiocarbon dating can be traced back to the 1960s. However, its reliability has recently been called into question. Piperno summarized recent dating evidence, but most phytolith dating results from China were not included in the review because they are written in Chinese. Herein, we summarize and evaluate previous phytolith dating results from China. We also review recent debates on the nature and origin of phytolith-occluded carbon (abbreviated as PhytOC) as well as the older age of phytoliths retrieved from modern plants. We conclude that although PhytOC includes a small amount of old carbon absorbed from the soil, this carbon fraction has not always biased phytolith ages, indicating that in certain situations, phytoliths can be tried as an alternative dating tool in archaeological and paleoecological research when other datable materials are not available.